2006
DOI: 10.1017/s0031182006000400
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of motor proteins in the muscles and flame cells of the Schistosoma mansoni miracidium and primary sporocyst

Abstract: Schistosoma mansoni eggs, miracidia and primary sporocysts were labelled with phalloidin-rhodamine to visualize filamentous actin structures. Analysis of these forms by confocal fluorescence microscopy revealed the presence of previously well-defined circular and longitudinal muscle layers. Besides these muscular layers that sustain and provide motility to these parasite forms, we found in these 3 consecutive developmental stages of the parasite previously unidentified actin-rich tubular structures. In the 3 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
4
21
0
2
Order By: Relevance
“…Flamecell differentiation seems to occur late during organogenesis (perhaps starting at stage 7), but additional investigations are still needed to clarify its emergence. Bahia et al (2006) have recently revealed the distribution of motor proteins in the musculature and flame cells of miracidia and primary sporocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Flamecell differentiation seems to occur late during organogenesis (perhaps starting at stage 7), but additional investigations are still needed to clarify its emergence. Bahia et al (2006) have recently revealed the distribution of motor proteins in the musculature and flame cells of miracidia and primary sporocysts.…”
Section: Discussionmentioning
confidence: 99%
“…For visualization of the musculature by f-actin, larvae were stained with Alexafluor 488-conjugated phalloidin (Invitrogen, Molecular Probes) and counterstained with DAPI according to the protocol of Bahia et al (2006). Specimens were fixed for 1 h in 4% paraformaldehyde in phosphate buffered saline (PBS) on ice and then permeabilized for 1 h in PBS, 0.2% gelatin, 0.1% saponin, 0.1% NaN 3 at room temperature, before staining, and washed several times in PBS before viewing.…”
Section: Whole-mount In Situ Hybridization and Immunocytochemistrymentioning
confidence: 99%
“…The corollary is that "there is a higher level of confidence that specific inhibitors can be designed to target protein kinases with < 60% sequence identity, which is the case for the vast majority of parasite kinomes when compared to that of humans" (Vieth et al 2004, Naula et al 2005 The presence of SmFes (in green) can be observed in terebratorium (miracidia) (A) and in oral sucker and acetabular gland (schistosomula) (B) (unpublished results). Actin (red) and DAPI (blue) labellings were obtained according to Bahia et al (2006b).…”
Section: Presence Of Pks In Sequenced Genomesmentioning
confidence: 99%